Role of repeat head computed tomography in the management of mild traumatic brain injury patients with a positive initial head ct - Ashraf, Sharifuddin (2010)
The advent of computed tomography (CT) has revolutionized the approach to mild traumatic brain injured (MTBI) patients. CT scan has now become standard practice in the initial management of MTBI patients. Those with a positive initial head CT not requiring surgical intervention will be warded for continuous neurological observation. As a routine, a repeat head CT is frequently ordered within 24 to 48 hours, even without any clinical neurological deterioration in patients condition. The logic of this practice is questionable as convincing evidence is lacking. Indiscriminate ordering of radiological tests puts a strain on the healthcare system, especially so in Malaysia since less than 30 government hospitals nationwide are equipped with CT scans. Therefore, the objective of this study is to evaluate the role of routine repeat head CT in providing useful information that leads to a neurosurgical intervention. This is a prospective observational study of MTBI patients admitted to the Neurosurgical ward, Sultanah Aminah Hospital, Johor Bahru from 1st June 2008 to 30th September 2009. A total of 279 patients was included in the study after meeting the inclusion criteria. MTBI is defined as Glasgow Coma Scale (GCS) score of 13, 14 or 15, with at least one of the following; head trauma with loss of consciousness lasting < 30 minutes; Glasgow Coma Scale score of 13 or more; post-traumatic amnesia lasting < 24 hours; any mental alteration at time of injury; and/or any transient or persistent neurological signs. A head CT is considered positive if there was a suspicion or clear evidence of an intracranial pathology. The result of the first head CT were obtained from the radiological report from this hospital's radiologist, or when not available, from the attending neurosurgeon's interpretation as documented in the case notes. The patient's demographic data, initial neurological examination findings, and biochemical analyses were documented. Neurological status was also documented until discharge. The results of the repeat head CT scan were obtained from the radiological report from the hospital's radiologist or from the attending neurosurgeon's notes. These were categorized as improved, unchanged or worsened. Any other additional neuroradiologic imaging or neurosurgical interventions were noted until discharge. Patients were divided into two groups, one with an unchanged or improving repeat head CT (n = 217) while the other with a worsened repeat head CT (n = 62). 31 patients received urgent surgical intervention after the repeat head CT was done. In all cases, neurological deterioration preceded and prompted an urgent repeat head CT. When the 62 patients with the worsened repeat head CT were compared to the other 217 patients, they were found to have significant statistical correlation with older age ( ~ 65 years old) (p value< 0.001), lower GCS on admission (p value= 0.003), associated symptoms of headache (p value= 0.019), multiple lesion on initial head CT (p value = 0.001), haemoglobin levels on admission (p value = 0.009), longer hospital stay (p value< 0.001), higher mortality rate (p value= 0.001), higher risk to undergo surgical intervention (p value < 0.001) and higher risk for neurological deterioration (p value < 0.001 ). There was no significant difference on gender, ethnic groups, mechanism of injury, other associated symptoms on admission, types of intracranial injury on initial head CT, types of skull fracture sustained and International Normalized Ratio levels. On applying multiple logistic regression, three factors were found to independently predict a worse repeat head CT. This includes age 2: 65 years old, GCS of less than 15 (i.e. 13 or 14) and multiple lesions on initial head CT. The role of a repeat head CT in MTBI patients with a positive initial head CT have been evaluated in this study. Without a clinical neurological deterioration, a repeat head CT did not change the surgical outcome of patients. Patients with a GCS of 13 - 15 can be easily observed and assessed in the neurosurgical ward, therefore it is unnecessary to order a repeat head CT in all MTBI patients. Due vigilance is warranted in those with risk factors for a worsening repeat head CT.